Concurrent vision and hearing impairment associated with cognitive dysfunction in a population aged 85+ years: the Ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iuliia A.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Bolshakova, Natalia I.; Safiullina, Kamilia R.; Gizzatov, Ainur V.; Ponomarev, Ildar P.; Yakupova, Dilya F.; et al. (BMJ open, 2022)
Objective To assess the prevalence of vision impairment, hearing impairment and dual sensory impairment (DSI) as combination of vision and hearing impairment, in association with cognitive dysfunction in a population aged 85+ years. - Methods The cross-sectional population-based Ural Very Old Study, conducted in rural and urban Bashkortostan, Russia, between 2017 and 2020, included a detailed ocular and systemic examination with assessment of moderate to severe vision impairment (MSVI)/blindness (best-corrected visual acuity <6/18), moderate to severe hearing loss (MSHL) and cognitive function. - Setting A rural and urban area in Bashkortostan, Russia. - Participants Out of 1882 eligible individuals aged 85+ years, 1526 (81.1%) individuals participated. - Primary and secondary outcome measures Prevalence of vision, hearing and DSI and cognitive dysfunction. - Results The study included 731 (47.9%) individuals (mean age 88.1±2.7 years; median 87 years, range 85-98 years) with measurements of MSVI/blindness, MSHL and cognitive function. The prevalence of MSVI/blindness, MSHL, DSI and dementia were 51.8% (95% CI 48.2% to 55.5%), 33.1% (95% CI 29.7% to 36.5%), 20.5% (95% CI 17.8% to 23.5%) and 48.2% (95% CI 44.5% to 51.8%), respectively. Lower cognitive function score was associated with lower visual acuity (p<0.001) and higher hearing loss score (p=0.03), after adjusting for older age (p=0.001), rural region of habitation (p=0.003), lower educational level (p<0.001) and higher depression score (p<0.001). Higher dementia prevalence was associated with higher MSHL prevalence (OR 2.18 95% CI 1.59 to 2.98; p<0.001), higher MSVI/blindness prevalence (OR 2.09, 95% CI 1.55 to 2.81; p<0.001) and higher DSI prevalence (OR 2.80, 95% CI 1.92 to 4.07; p<0.001). - Conclusions In this very old, multiethnic population from Russia, DSI (prevalence 20.5%), as compared with hearing impairment (OR 2.18) and vision impairment alone (OR 2.09), had a stronger association (OR 2.80) with dementia. The findings show the importance of hearing and vision impairment, in particular their combined occurrence, for dementia prevalence in an old population.